2015
DOI: 10.1063/1.4906747
|View full text |Cite
|
Sign up to set email alerts
|

Doped GaN nanowires on diamond: Structural properties and charge carrier distribution

Abstract: In this work, we present a detailed study on GaN nanowire doping, which is vital for device fabrication. The nanowires (NWs) are grown by means of molecular beam epitaxy on diamond (111) substrates. Dopant atoms are found to facilitate nucleation, thus an increasing NW density is observed for increasing dopant fluxes. While maintaining nanowire morphology, we demonstrate the incorporation of Si and Mg up to concentrations of 9× 1020cm−3 and 1 × 1020cm−3, respectively. The dopant concentration in the nanowire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…14,33 However, the surface states should not affect the conductivity of the highly doped GaN nanodisks, where the band bending is restricted to a few nanometers close to the surface. 34 The persistent phenomena are rather associated to the stem/cap GaN segments, which are fully depleted in the dark and where a conductive channel is opened under illumination. The decelerated discharging of surface states should thus delay the restoration of full depletion of these parts of the structure.…”
mentioning
confidence: 99%
“…14,33 However, the surface states should not affect the conductivity of the highly doped GaN nanodisks, where the band bending is restricted to a few nanometers close to the surface. 34 The persistent phenomena are rather associated to the stem/cap GaN segments, which are fully depleted in the dark and where a conductive channel is opened under illumination. The decelerated discharging of surface states should thus delay the restoration of full depletion of these parts of the structure.…”
mentioning
confidence: 99%
“…Lefebvre et al have reported a strong influence on the PL intensity of bare GaN NWs under different atmospheres. 13 In particular, 20 The growth parameters applied for NWs on diamond are equivalent to those on Si substrate. However, GaN NW growth on diamond is characterized by a slightly thicker diameter of the NWs compared to NWs on Si due to an enhanced lateral growth (SEM images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While substrate and dopant Si could not be separated, extremely high Mg concentrations were determined in the NWs by secondary ion mass spectrometry (SIMS). With diamond substrates, it was possible for the first time to perform SIMS measurements without an interfering influence of the substrate [59].…”
Section: Doping Characteristicsmentioning
confidence: 99%
“…A brief summary of surface segregation will be given in the following whereas readers are referred to Ref. [59] for more information about the other effects.…”
Section: Doping Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation